Physiologically Beneficial Actions of Alliin in Health and Disease - Torres-Reyes, Daniel Ulises; Sánchez-Sánchez, Alma Marina; Carrera-Quintanar, Lucrecia; Ortuño-Sahagún, Daniel (Current Nutraceuticals, 2022)
Background Garlic has been considered to have medicinal properties in different cultures since ancient times. Vegetables of the allium genus are a natural source of sulfur-containing organic compounds. These compounds have recently been investigated for their positive health effects, such as antioxidant and anti-inflammatory, as well as cardioprotective and anticarcinogenic properties. Objective In this review, we focus on one of the main components of garlic; alliin or S-allyl-L-cysteine sulfoxide, which is a non-protein amino acid that exhibits a broad spectrum of beneficial effects on physiology, both at the cellular and whole organism levels. Methods We conducted a systematic literature search of the MEDLINE (PubMed) database. Search terms used for alliin were: “S-allylcysteine sulfoxide” OR “L-alliin” OR “ACSO”, all of them combined into a separated search term individually as follows: AND “antioxidant”; AND “cardioprotective”; AND “anti-inflammatory”; AND “antimicrobial”; AND “disease”, and; AND “neuroprotective”. Results Here, we review and integrate the existing experimental evidence on the effects of alliin, mainly on its antioxidant and anti-inflammatory effects, as well as its cardioprotective action, and its role as an adjuvant for the treatment of different diseases, such as infectious diseases, inflammatory diseases, metabolic diseases and cancer. Conclusion Finally, we propose alliin as a possible neuroprotective agent, through the combination of its antioxidant and anti-inflammatory effects, and its ability to reduce markers of metabolic inflammation in obesity.
Keywords: neuroinflammation